A rare case of myotonic dystrophy type 1 presenting with Torsades de pointes - Amit Handa; Rinki Kakkar (IHJ Cardiovascular Case Reports, 2023)
Myotonic Dystrophy (DM) is the most common form of muscular dystrophy with onset in adults. Cardiac manifestations are common in DM, but ventricular arrhythmias are uncommon and torsades de pointes is rarely described. Here we describe a patient with primary presentation of syncope, with recurrent polymorphic ventricular tachycardias and with torsades de pointes configuration.